STRATEGI PENYELESAIAN PEMBIAYAAN BERMASALAH BERBASIS ISLAMIC ENTREPRENUERSHIP DI BMT SE-KOTA JEPARA - solikhulhidayat; Muhammad Zaid Alaydrus; Masykuri Bakri (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
Most BMTs in Jepara City experience problematic financing, the high level of NPF (Non Performing Financing) on ​​average reaches above 26%, even though BMT health requires no more than 5%, this is very risky. Failure to repay financing, if not addressed immediately, will have a negative impact on BMT, poor financial performance and a more serious threat to the survival of BMT. This research is to find out the causes of problematic financing and how to solve it. By using a qualitative descriptive study. 12 BMTs in Jepara City who are members of the NU Citizens' Sharia Cooperative Association (Askowanu) as research objects. From the results of the study, the main factors causing non-performing financing are because customers have difficulty paying installments due to non-current businesses, lack of skills in running a business, use of funds that are not in accordance with planning, loan funds are often used for something unproductive, borrower delinquency, from the start. had bad intentions in applying for financing. The existence of these problems is seen from the perspective of Islamic Entrepreneurship, of course it is not appropriate. The strategy for solving problem financing carried out by BMT is through rescheduling, reconditioning, restructuring, another strategy is through the NU organizational path, by means of a personal approach. In the future, to overcome these problems, intensive assistance and supervision is needed as well as providing an understanding of Islamic entrepreneurs who prioritize honesty and trust.